Inclusive Playground for Children with Disabilities to Promote Social Sustainability - Mohd Aizat Akhmal Bin Raja Mohd Rozuan, Raja; Ismail , Kharizam; Rabiah Wan Omar, Wan (International Journal of Psychosocial Rehabilitation, 2020)
Playing is a vital component for the development of children in the sense of effectiveness, psychomotor, cognitive skill, social interaction and creativity. All children, including children with disabilities, have the rights to the experience of play towards their development. Disabled children required this even more than others. However, nowadays, children with disabilities often face problems at public playgrounds, entertainment places, and amusement areas, due to the lack of ample provisions to cater to their special needs. Commonly, children with disabilities have physical disabilities that involve difficulties in walking, mobility, sitting, standing, and other significant weaknesses which create the barrier and exclusion between normal children and these disabled children. In Malaysia, there had been no studies on the needs of a proper sustainable design model for public playgrounds to cater to children with disabilities. The challenge ahead for Malaysia is to transform its approach from a welfare perspective to human rights. Based on the hurdles, the research objective was highlighted to identify the criteria of the accessible playground as the guideline of the inclusive playground for children with disabilities to achieve social sustainability. A qualitative method was used for this research that is by observing the condition of an inclusive playground in Penang. The outcomes of this research are expected to assist the stakeholder Municipal Council to influence the inclusiveness of the elements in the playground to attract more children with disabilities to play on the playground thus to widen the social sustainability towards the society.